2010
DOI: 10.1029/2010gl043216
|View full text |Cite
|
Sign up to set email alerts
|

Can internal processes sustain reversals of the ocean upper circulation? The Ionian Sea example

Abstract: In 1997 an inversion in the Ionian upper‐layer circulation was documented and ascribed to a massive inflow of Aegean dense waters associated with the Eastern Mediterranean Transient (EMT) and not to the wind‐stress (Borzelli et al., 2009). Here we generalize the concept hypothesizing that such inversions are possible even in the absence of the Aegean influence. Indeed, salinity and density data collected in the Southern Adriatic, the main source of the Eastern Mediterranean deep water, show decadal variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
276
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 248 publications
(289 citation statements)
references
References 18 publications
13
276
0
Order By: Relevance
“…These reversals are related to the spatial variability of the meandering AIS along with the respective reduction or restoration of the LIW/CIW flow in the North Ionian. The thermohaline pump mechanism proposed by Theocharis et al, [2014] differs from the BiOS mechanism proposed by Gačić et al [2010Gačić et al [ , 2011 Krokos et al [2014] showed that this pumping mechanism is an ongoing internal mechanism that led to the reactivation of the Aegean Sea during 2007-2009 almost a decade after the end of the EMT production period. Both Theocharis et al, [2014] and Krokos et al [2014] argue that the role of the internal mechanism seems to prevail over the long-term atmospheric influence in DWF events in the EMed.…”
Section: Deep Water In the Cretan Sea And The Eastern Mediterranean Tmentioning
confidence: 58%
See 1 more Smart Citation
“…These reversals are related to the spatial variability of the meandering AIS along with the respective reduction or restoration of the LIW/CIW flow in the North Ionian. The thermohaline pump mechanism proposed by Theocharis et al, [2014] differs from the BiOS mechanism proposed by Gačić et al [2010Gačić et al [ , 2011 Krokos et al [2014] showed that this pumping mechanism is an ongoing internal mechanism that led to the reactivation of the Aegean Sea during 2007-2009 almost a decade after the end of the EMT production period. Both Theocharis et al, [2014] and Krokos et al [2014] argue that the role of the internal mechanism seems to prevail over the long-term atmospheric influence in DWF events in the EMed.…”
Section: Deep Water In the Cretan Sea And The Eastern Mediterranean Tmentioning
confidence: 58%
“…Theocharis et al, [2002a] observed a few years after the EMT (1997-1999) a reversal of the upper layer circulation in the Central Ionian Sea which returned to the pre-EMT cyclonic pattern, while AW re-established its pre-EMT eastward flow toward the Levantine. Further studies [Borzelli et al, 2009;Gačić et al, 2010Gačić et al, , 2011Poulain et al, 2012] have confirmed that in both 1997 and 2006 the Ionian Sea upper circulation demonstrated reversals and concluded that the changes in the Ionian Sea upper layer circulation pattern is a recurrent phenomenon occurring on an almost decadal time scale. Gačić et al [2010Gačić et al [ , 2011 proposed a feedback mechanism, named the Adriatic-Ionian Bimodal Oscillating System (BiOS), between the observed North Ionian upper layer circulation inversions and the water mass redistributions in the Ionian Sea which relate to variations of the thermohaline properties of waters formed in the Southern Adriatic Sea.…”
Section: Deep Water In the Cretan Sea And The Eastern Mediterranean Tmentioning
confidence: 73%
“…Core LC10 is only a few tens of kilometres from the Ionian Gyre ( Fig. 1) which seems to switch from a cyclonic to an anticyclonic configuration at a decadal scale, affecting the biological productivity in the northern Ionian and southern Adriatic Sea Gačić et al, 2010).…”
Section: Study Areamentioning
confidence: 99%
“…Recorded changes in Ionian Sea circulation, consisting in the mixing of higher salinity Aegean/Levantine water with lower salinity water of Atlantic origin (Gačić et al, 2010), could possibly explain the presence of Levantine and Atlantic species in the Eastern Adriatic Sea. This refers to Eastern Adriatic ichtyofauna in particular.…”
Section: Introduced Ichthyofauna In the Eastern Adriatic Seamentioning
confidence: 99%
“…It extends in a southeast -northwest direction, with a shallow northern part and a deeper southern part. Adriatic Sea ecosystems are influenced by regular exchange of water with the Mediterranean Sea (Gačić et al, 2010).…”
Section: Introductionmentioning
confidence: 99%